BlackBerry Bold Made Simple For the BlackBerry Bold 9700 and 9650 Series - Trautschold, Martin; Mazo, Gary.; Anglin, Steve; Markham, James; Andres, Clay.; Anglin, Steve; Beckner, Mark.; Buckingham, Ewan.; Cornell, Gary.; Gennick, Jonathan; Hassell, Jonathan; Lowman, Michelle; et al. (Berkeley, CA : Apress, 2010)
You$1 (Bve chosen well$1 (Bwith elegant design, a high-res display, and a speedy processor, the Bold is a top-notch device. Now learn how to take advantage of all the features with this easy-to-read guide from two of the best BlackBerry trainers in the business. BlackBerry Bold Made Simple teaches you how to get the most out of your BlackBerry Bold. You$1 (Bll explore all the features and uncover time-saving techniques$1 (Bfrom emailing and scheduling to video recording and expanding memory$1 (Ball through easy-to-read instructions and detailed visuals. Written by two successful BlackBerry trainers and authors, this is simply the most comprehensive and clear guidebook to the BlackBerry Bold available.s
Quick Start Guide -- Getting Around Quickly -- Congratulations on Your BlackBerry Bold! -- You and Your BlackBerry Bold -- Email Set Up -- Windows Pc Setup -- Windows Pc Media and File Transfer -- Apple Mac Setup -- Apple Mac Media and File Transfer -- Typing, Spelling and Help -- Speed Your Typing With AutoText -- Personalize Your BlackBerry -- Sounds: Ring and Vibrate -- Phone and Voice Dialing -- Advanced Phone -- Email Like a Pro -- Advanced Email Topic -- Your Contact List -- Managing Your Calender -- Get Tasks Done -- MemoPad: Seicky Notes -- SMS Text and MMS Messaging -- Even More Messaging -- Adding Memory with a Media Card -- Your Music Player -- Snapping Pictures -- Fun with Videos -- Social Networking -- Connecting with Wi-Fi -- BlackBerry App Workd -- Connecting with Bluetooth -- Connect as a Tethered Modem -- Serfing the Web -- Add or Remove Apps -- Travelling:Maps and More -- Other Applications -- Searching for Lost Stuff -- Searching for Data -- fixing Problems -- More Resources -- Hotkey Shortcuts -- Notkeys $1 (BOpen Almost Any App With One key!.s
Keywords: Computer science; Computer Science; Computer Science, general